The Potential of Flowering Weeds as Refugia for Predatory Insects at Bantimurung-Bulusaraung National Park, South Sulawesi - Sri Nur Aminah Ngatimin; Nurariaty Agus; Annie P. Saranga (Journal of Tropical Crop Science, 2014)
A study on identication of owering weeds as predatory insect alternative foods was conducted at Bantimurung- Bulusaraung National Park, South Sulawesi, Indonesia in February 2013. Among the plants that naturally grow in the national park area Cassia siamea and Clerodendron paniculatum, which were source of nectar for insects, particularly butteries. Visits of predatory insect to owering weeds and species of both insects and owering weeds were recorded. The preferred owering weeds visited by the predatory insects are C. striata (Papilionaceae), A.conyzoides (Asteraceae) and L. camara (Verbenaceae) followed by S. nodiflora (Asteraceae), S. rhombifolia (Malvaceae) and L. crustacea (Scrophulariaceae). A large number of adults and pupae of Coccinella sp. was found in the Bantimurung-Bulusaraung National Park.